1986
DOI: 10.1113/jphysiol.1986.sp016161
|View full text |Cite
|
Sign up to set email alerts
|

Plasma expansion does not precipitate the fall in plasma vasopressin in humans drinking isotonic fluids.

Abstract: SUMMARY1. In a group of healthy humans, plasma vasopressin (AVP) levels fell on drinking either Tyrode or mannitol solutions isosmotic with plasma. Both the timing and magnitude of the fall were appropriate to account for the transient diuresis which followed the drinking.2. Although plasma expansion follows drinking Tyrode solution it occurred too late to account for the fall in plasma AVP. It was also too small to inhibit AVP secretion.3. Even though plasma volume tended to contract on drinking isosmotic man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1988
1988
1992
1992

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
(17 reference statements)
0
6
0
Order By: Relevance
“…Since Tyrode solution is slowly absorbed activation of systemic volume receptors (Dunn, Brennan, Nelson & Robertson, 1973) could possibly augment or sustain the effects of the oropharyngeal signals on plasma AVP levels. In the present study we did not measure a fall in plasma AVP levels following the drinking of Golytely even though the assay used in this study was the same as that used in the study of Cotter et al (1986) and sufficiently sensitive to measure changes in plasma AVP of 0 6 pg ml-'. Furthermore measured levels of plasma AVP agreed well with those predicted by Robertson's equation (Robertson et al 1976) on the control morning and for the predrinking period on the test morning.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Since Tyrode solution is slowly absorbed activation of systemic volume receptors (Dunn, Brennan, Nelson & Robertson, 1973) could possibly augment or sustain the effects of the oropharyngeal signals on plasma AVP levels. In the present study we did not measure a fall in plasma AVP levels following the drinking of Golytely even though the assay used in this study was the same as that used in the study of Cotter et al (1986) and sufficiently sensitive to measure changes in plasma AVP of 0 6 pg ml-'. Furthermore measured levels of plasma AVP agreed well with those predicted by Robertson's equation (Robertson et al 1976) on the control morning and for the predrinking period on the test morning.…”
Section: Discussionmentioning
confidence: 92%
“…The excretion of a dilute urine is not only attributed to but has been shown to be due to a decrease in plasma AVP levels. A fall in plasma AVP has been observed following the drinking of Tyrode solution, though not sufficient to account for the magnitude of the diuresis (Cotter et al 1986). This fall was attributed to stimulation of oropharyngeal receptors which have been shown by a number of workers to decrease plasma AVP (Thrasher et al 1980;Geelan et al 1984).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cotter et al (1986) and Thrasher, Keil & Ramsey (1987) concluded that the effect of fluid on the oral cavity and oesophagus was the major factor in mediating this response. Our data support the contention that gastric distension may also be important, at least in rats.…”
Section: Discussionmentioning
confidence: 96%
“…The present experiments were undertaken to investigate this inter¬ action further and to establish whether increasing plasma volume by administration of isotonic saline would decrease the activity of cells in the supraoptic nucleus. Measurement of changes in haematocrit is an established method for detecting changes in plasma volume (Cotter, Gebruers, Hall & O'Sullivan, 1986).…”
Section: Discussionmentioning
confidence: 99%